Pemenuhan Kebutuhan Komunitas Maya Dan Pandu Digital Kepada Perangkat Desa di Desa Sindangpalay - Hidayat, Miftahul; Multajam, Sri Intan; Adha, Sherly Nabila; Andyarini, Ervina Dwi; Farhan, Muhammad; Aulia, Husni; Sidiq, Repi Fahmi; Nisa, Ziadatun Khoirun; Firmanto, Alam; Afifah, Via Nur; Agustin, Yoga Handoko (Institut Teknologi Garut, 2022)
Real Work Lecture (KKN) is a form of community service activity by students with an cross-scientific and sectoral approach at a certain time and area. The implementation of KKN activities usually lasts between one to two months and takes place in village-level areas. And the purpose of KKN is so that students can develop ideas based on technology and in an effort to grow, accelerate and prepare development cadres, students gain valuable learning experience through involvement in the community which directly discovers, formulates, solves and tackles development problems in a practical and interdisciplinary, to add insight. Students motivate the community in building villages, to provide experience to students about ways of being in society. The existence of Real Work Lectures has a target so that students can become a ready-to-use generation and at the same time potential successors to development, especially in rural areas, both in the present and in the future. And this report aims to show the results of the KKN activities during the Covid-19 pandemic which we carried out in about a month. Webinars for Virtual Communities. This report also contains information about Sindangpalay Village, where we carried out KKN activities.